Volume 4: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-28173
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Turbulent Flow in 180° Turning Ducts With and Without Guide Vanes

Abstract: This paper presents a numerical study of the turbulent flows through a number of 2-D and 3-D 180° U-ducts, with and without guide vanes, using the Reynolds-averaged Navier-Stokes method. Computations have been first carried out for a 2-D U-duct flow (W/H = 1.0) with four turbulence models (V2F, k-ε, SST and Reynolds stress). The models’ capability for streamline curvature effects on turbulence and separation has been assessed, using flow and turbulence data. The effects of adding a guide vane inside the bend h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Luo and Razinsky [17] presented a numerical study of the turbulent flow through an 180°sharp turn and a U-bend, respectively, with or without a turning vane. Their results of with the turning vane showed that the separation zone near the inner wall right after the turn is substantially reduced and the secondary flow kinetic energy (SKE) is also reduced by 38%.…”
Section: Turning Vane Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo and Razinsky [17] presented a numerical study of the turbulent flow through an 180°sharp turn and a U-bend, respectively, with or without a turning vane. Their results of with the turning vane showed that the separation zone near the inner wall right after the turn is substantially reduced and the secondary flow kinetic energy (SKE) is also reduced by 38%.…”
Section: Turning Vane Effectmentioning
confidence: 99%
“…It was concluded that heat transfer could increase as much as 65% while pressure drop could either decrease or increase depending on the specific configuration. The investigations [17][18][19][20] were all performed under non-rotation conditions.…”
Section: Turning Vane Effectmentioning
confidence: 99%
“…In 2003, James D. Heidmann [4] developed coupling heat exchange solver and applied it in an air-cooled turbine stator blade with many kinds of materials. Jiang Luo and Eli H. Razinsky [5] used conjugate heat transfer analysis method to predict flow and the metal temperature of NASA turbine stator under the operation condition. Although the overall coincide was good, it should also be pointed out that there is room to improve for V2F model they used in the prediction of boundary layer transition and turbulent heat transfer especially in the suction surface.…”
Section: Introductionmentioning
confidence: 99%